2019
DOI: 10.3390/ma12091408
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition Characteristics of SF6 under Flashover Discharge on the Epoxy Resin Surface

Abstract: In this paper, the flashover discharging experiment was carried out on epoxy resin surface in an SF6 atmosphere under pin-plate electrodes, with the electrodes distance from 5 mm to 9 mm. The concentration of seven characteristic gases was detected, indicating that the concentration of SOF2 and CF4 was the two highest, followed by SO2, CO2, SO2F2, CS2, and H2S. Based on the changes in the concentration of the characteristic gases, a preliminary rule was proposed to predict the occurrence of flashover discharge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…A reduction of glass transition temperature means the polymer can be softened at a lower temperature and the effect of reduced thermal stability and yield strain or stress may promote electrical tree growth. It was reported that gas by-products such as SOF2, CF4, SO2, CO2, SO2F2, CS2 and H2S were generated in flashover tests with epoxy resin in SF6 [10]. Simulation of decomposition in epoxy resin in ReaxFF program shows that H2O, H2, CO2, CH2O CO and CH4 are the major by-products at 1300 K. Gas by-products such as SOF2 and SF4 can react with H2O and form hydrogen fluoride (HF) [11].…”
Section: Discussionmentioning
confidence: 99%
“…A reduction of glass transition temperature means the polymer can be softened at a lower temperature and the effect of reduced thermal stability and yield strain or stress may promote electrical tree growth. It was reported that gas by-products such as SOF2, CF4, SO2, CO2, SO2F2, CS2 and H2S were generated in flashover tests with epoxy resin in SF6 [10]. Simulation of decomposition in epoxy resin in ReaxFF program shows that H2O, H2, CO2, CH2O CO and CH4 are the major by-products at 1300 K. Gas by-products such as SOF2 and SF4 can react with H2O and form hydrogen fluoride (HF) [11].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the chamber was filled with fresh SF 6 to reach the desired pressure value, making sure that most of the water vapor and air were removed. Thus, the purity of the SF 6 used during the experiments could be guaranteed [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…Yang et al found that when there are particles attached to the epoxy surface, the discharge of the particles will destroy the covalent bonds on the surface during the long-term degradation process, resulting in a decrease in the trap energy level [10]. Wen et al carried out the effect of degradation on the microstructure of materials due to AC discharge, and their proposed epoxy cleavage products include H 2 O and CH 4 , and their formation mechanisms include reactions involving free radicals, demethylation reactions, etc [11]. However, the degradation mechanism due to discharge differs from that due to the electric field and heat.…”
Section: Introductionmentioning
confidence: 99%